Answer:
d
Step-by-step explanation:
given the 2 equations
y = x² + 3 → (1)
3x - y + 1 = 0 → (2)
substitute y = x² + 3 into (2)
3x - (x² + 3) + 1 = 0
3x - x² - 3 + 1 = 0
-x² + 3x - 2 = 0 ( multiply through by - 1 )
x² - 3x + 2 = 0 ← in standard form
(x - 1)(x - 2) = 0 ← in factored form
equate each factor to zero and solve for x
x - 1 = 0 ⇒ x = 1
x - 2 = 0 ⇒ x = 2
Substitute each value into (1) for corresponding values of y
x = 1 : y = 1 + 3 = 4 → (1, 4)
x = 2 : y = 4 + 3 = 7 → (2, 7)
solutions are (2, 7), (1, 4) → d